International entrepreneurship in emerging markets : nature, drivers, barriers and determinants - Haddoud, Mohamed Yacine; Jones, Paul; Onjewu, Adah-Kole Emmanuel (Contemporary issues in entrepreneurship research ;, 2019)
Among several themes in contemporary entrepreneurship, internationalisation generates extensive interest among scholars due to its exploration of dynamic activity within SMEs seeking market development and operational efficiency through foreign alliance and intelligence gathering opportunities. In the context of emerging markets, however, international entrepreneurship scholarship still lags behind first world evidence. With less developed avenues for finance and limited infrastructure support for product development and service delivery, an assessment of internationalisation within emerging contexts is required.International Entrepreneurship in Emerging Markets presents insights from Brazil, China, India, Pakistan, Sri Lanka and Turkey to enlighten scholars by unearthing the nature, drivers, barriers and determinants of entrepreneurship in emerging markets. It examines structural and environmental impediments to internalisation but demonstrates that these are far surpassed by the market opportunities and business readiness of SMEs in emerging environments. Readers of this tenth volume of the Contemporary Issues in Entrepreneurship Research series will find exclusive evidence from emerging countries, evidence that demonstrates the inclination of SMEs to revise products and, when appropriate, dissolve and recreate relationships in the face of market opportunity and uncertainty. Managers will learn that appropriating a range of attributes are more likely to achieve internationalisation.Capturing the true nature of value creation for international consumers and partners in an emerging market backdrop, this volume makes a significant contribution to the literature by mapping out the road to success within this diverse setting.